STRATEGI PEMANFAATAN POTENSI DAERAH DI KABUPATEN WONOGIRI SEBAGAI UPAYA MENINGKATKAN KEMANDIRIAN FISKAL DAERAH - Chairunnisa, Meisyarah Alifah; Darmawan, Darmawan (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Wonogiri Regency is one of the regions with very low fiscal independence. A strategy to optimize the existing potential is needed to reduce the level of dependence on the central and provincial governments through PAD. This research is a qualitative study of the study of regional potential based on mapping that has been carried out by BPS. Then, strategy design is carried out using SWOT analysis to provide alternative aggressive, turn, diversification, and defensive strategies. The results of this analysis show that the most potential sector to increase fiscal independence through PAD is the manufacturing industry. The strategies that can be applied to develop this sector are increasing investment in infrastructure and education, cooperation between local governments, processing industries, and educational institutions, and effective promotion and branding